The Impact of Corporate Sustainability Initiatives and Public Governance on Corporate Carbon Performance: A Case Study of Companies in ASEAN Countries - Pana Sabila; Sofik Handoyo; Gia Kardina Prima Amrania (Eduvest - Journal of Universal Studies, 2026)
This study examines the impact of Corporate Sustainability Initiatives (CSI) and Public Governance on corporate carbon performance in ASEAN countries. The research focuses on internal sustainability initiatives represented by green innovation and resource efficiency, as well as external governance factors measured by regulatory quality and government effectiveness. Using a quantitative approach, this study analyzes companies operating in the energy, materials, and industrial sectors across Indonesia, Malaysia, Singapore, Thailand, and the Philippines. Secondary data were obtained from Refinitiv Eikon and the Worldwide Governance Indicators, and the relationships among variables were tested using Structural Equation Modeling with Partial Least Squares (SEM-PLS). The findings indicate that resource efficiency has a positive and significant effect on corporate carbon performance, highlighting the importance of operational efficiency in reducing carbon emissions. In contrast, green innovation does not show a significant effect, suggesting that green innovation in ASEAN firms tends to be symbolic rather than transformational. Furthermore, government effectiveness demonstrates a significant negative relationship with carbon intensity, implying that more effective governance is associated with better carbon performance. Regulatory quality, however, does not show a significant effect. Firm size positively affects carbon performance, while leverage shows no significant effect. Overall, the results emphasize that improving corporate carbon performance in ASEAN requires a combination of substantive internal sustainability initiatives and effective public governance. This study contributes to the sustainability and governance literature by providing empirical evidence from a developing regional context and offers practical insights policymakers and corporate managers in designing effective strategies to achieve carbon reduction goals.